Effects of collaborative digital media on the critical and creative thinking of grade 10 students - Sarmiento, Francesca Isabelle Besinga; Oyzon, Maria Vanessa P. Lusung; Muega, Michael Arthus G.; Que, Elenita N. (Quezon City College of Education, University of the Philippines Diliman, 2020)
This study explored if collaborative digital media (CDM) as a strategy in values education, has significant effect on the critical and creative thinking on grade 10 students. A critical and creative thinking scale was administered before and after the students exposure to CDM for an entire quarter, to determine if there is any significant difference in the pre-test and posttest scores. Guided use of CDM was done through carefully executed lesson plans and thoroughly crafted techniques in order for the students to stay focused and to direct reap the benefits of CDM in learning. In addition to the students scores, content analysis was done on their responses in the focus group discussions and individual questionnaires. Both the quantitative and qualitative methods of research and analysis found CDM to be significantly beneficial in enhancing the students critical thinking and creative thinking skills.
Thesis
Includes bibliographical references (pages 79-86)
Keywords: Values -- Study and teaching (Secondary) -- Philippines -- Manila Metropolitan Area; Digital media -- Philippines -- Manila Metropolitan Area; Critical thinking in children -- Philippines -- Manila Metropolitan Area; Creative thinking in children -- Philippines -- Manila Metropolitan Area; Education -- Effects of technological innovations on -- Philippines -- Manila Metropolitan Area; Educational technology -- Philippines -- Manila Metropolitan Area; Teaching -- Philippines -- Manila Metropolitan Area -- Aids and devices; Critical and creative thinking scale